Book Reviews. Issue 2 (1st December 2020) - Baker, Lucy; Castañeda, Paola; Dalstrom, Matthew; Datta, Ankur; Joelsson, Tanja; Jordi-Sánchez, Mario; Kelly, Jennifer Lynn; Zunino Singh, Dhan
Abstract : Nicholas A. Scott, Assembling Moral Mobilities: Cycling, Cities and the Common Good (Lincoln: University of Nebraska Press, 2020), 288 pp., 38 illus., $50 John Stehlin, Cyclescapes of the Unequal City: Bicycle Infrastructure and Uneven Development (Minneapolis: University of Minnesota Press, 2019), 328 pp., 24 photos, 11 maps, 9 tables, $27 Cecilia Vindrola-Padros, Critical Ethnographic Perspectives on Medical Travel (New York: Routledge, 2019), 161 pp., $36.77 Nicola Frost and Tom Selwyn, eds., Travelling Towards Home: Mobilities and Homemaking (New York: Berghahn, 2018), 182 pp., 10 illus., 1 table, $110 Peter Cox, Cycling: A Sociology of Vélomobility (Abingdon: Routledge, 2019), 200 pp., 2 B/W illus., £120.00 (ebook £40.49) Lesley Murray and Susana Cortés-Morales, Children's Mobilities: Interdependent, Imagined, Relational (London: Palgrave Macmillan, 2019), 307 pp., 10 illus., $89.99 Jocelyne Guilbault and Timothy Rommen, eds., Sounds of Vacation: Political Economies of Caribbean Tourism (Durham, NC: Duke University Press, 2019), 234 pp., $25.95 John Krige, ed., How Knowledge Moves: Writing the Transnational History of Science and Technology (Chicago: The University of Chicago Press, 2019), 408 pp., 11 illus., $40